Paraclostridium benzoelyticum Bacterium-Mediated Zinc Oxide Nanoparticles and Their In Vivo Multiple Biological Applications. (5th May 2022) - Faisal, Shah; Abdullah,; Rizwan, Muhammad; Ullah, Riaz; Alotaibi, Amal; Khattak, Aishma; Bibi, Nadia; Idrees, Muhammad
Abstract : We presented a low-cost, eco-friendly, and efficient bacterium-mediated synthesis of zinc oxide nanoparticles (ZnO-NPs) utilizing Paraclostridium benzoelyticum strain 5610 as a capping and reducing agent. Scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, energy-dispersive X-ray, and UV-vis spectroscopy were used to physiochemically characterize the biosynthesized ZnO-NPs. A major narrow peak at 441 nm was observed using UV-visible spectroscopy, verifying the presence of nanoparticles. According to SEM and TEM studies, the average dimensions of ZnO-NPs was 50 nm. The crystal size of 48.22 nm was determined by XRD analysis. FTIR analysis confirmed the presence of various reducing metabolites on the surface of ZnO-NPs. The synthesized nanoparticles were investigated for biological activity against Helicobacter suis, Helicobacter bizzozeronii, Helicobacter felis, and Helicobacter salomonis. Helicobacter suis was the most vulnerable strain, with an inhibitory zone of 19.53 ± 0.62 mm at 5 mg/mL dosage. The anti-inflammatory and the findings of the rat paw edema experiments revealed that the bacterium-mediated ZnO-NPs had a strong inhibitory action. In the arthritis model, the solution of ZnO-NPs showed 87.62 ± 0.12 % inhibitory effect of edema after 21 days when linked with that of the standard drug. In the antidiabetic assay, ZnO-NPs sharply reduced glucose level in STZ-induced diabetic mice. In this study, the particle biocompatibility by human red blood cells was also determined. Keeping in view the biological importance of ZnO-NPs, we may readily get the conclusion that Paraclostridium benzoelyticum strain 5610-mediated ZnO-NPs will be a prospective antidiabetic, antibacterial, antiarthritic, and anti-inflammatory agent in vivo experimental models and can be used as a potent antidiabetic drug.